2018
DOI: 10.1080/00016489.2017.1380312
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional bleomycin A5 injection for the treatment of nasal polyps through inducing apoptosis

Abstract: After several local injections of BLE, the nasal polyp tissues decreased and then disappeared. During follow-up of 3 years the recurrence rate of this group was significantly lower than another one treated with operation plus medicine treatment. Apoptosis in BLE-treated tissue was prominently detected in the infiltrating inflammatory cells. The expression of PARP and casp-8 were increased in BLE-treated nasal polyp tissue compared with PBS-treated tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“… 30 In another study, the expression of PARP and caspase 8 were increased in bleomycin-treated NP tissue; also the tissues were decreased and then disappeared. 31 …”
Section: Discussionmentioning
confidence: 99%
“… 30 In another study, the expression of PARP and caspase 8 were increased in bleomycin-treated NP tissue; also the tissues were decreased and then disappeared. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we tested genotoxic and cytotoxic effects in BLE-A5-treated NPDF in our previous researches, including DNA smear testing, cell cytotoxicity assay and cell immigration assay. We found that BLE-A5 can induce DNA fragmentation, reduce cell viability and suppress proliferation in NPDFs (24,27). We also found that NPdF is more sensitive to BLE-A5 administration compared with normal nasal mucosa derived fibroblasts (NMDF) (28).…”
Section: Introductionmentioning
confidence: 75%
“…NP tissue preparation and treatment were performed as described in our previous study (24). After BLE-A5 treatment, a midsagittal section of formalin-fixed (4% at room temperature for 1 h), paraffin-embedded nasal polyp tissue was permeabilized with 0.1% Triton X-100.…”
Section: Immunofluorescence Analysis Of Np Fibroblasts and Epithelialmentioning
confidence: 99%
“…Other therapies pursued in the literature for the treatment of CRSwNP, but not reviewed here, include small molecules such as verapamil, intralesional bleomycin, topical tretinoin, metformin, and phototherapy. [79][80][81][82][83]…”
Section: Additional Therapiesmentioning
confidence: 99%